EVALUASI HIDDEN CURRICULUM DI SMP NEGERI BOJA, KABUPATEN KENDAL - Lestari, Neni; Sulasmono, Bambang Suteng (Kelola: Jurnal Manajemen Pendidikan, 2015)
This study aimed to evaluate the implementation and impact of Hidden Curriculum,Â as well as the determinant factors of success and sustainability in SMPN 2 BojaÂ Kendal. This study was an evaluative research using qualitative approach. The dataÂ collected by using observation, interviews, and documentation. Data analyzed byÂ collecting and selecting to be deduce. Validity used triangulation data that combinedÂ the result of observation, interviews, and documentation. The results of the studyÂ were: 1) The activities of hidden curriculum development at SMPN 2 Boja Kendal,Â namely: flag ceremony, school environmental management, establishing and enforcingÂ discipline, special religious worship, smiles, greetings and courtesies, exemplary,Â relationship among students and principal, teachers, and staff, school canteenÂ services. 2) The impact of the hidden curriculum development was the changing of school communityâs behavior being better, created clean and beautiful school environment, the improvement of public trust to the school toward their kidsâ education.Â Development of the hidden curriculum could establish students good character andÂ an optimal achievement as well as a good school culture. 3) Internal supportingÂ factors including: qualified human resources, the availability of school facilities,Â school environment was clean and beautiful. External supporting factors occur inÂ the form of endorsement of the parents, school committees and communities inÂ establishing good and virtuous character for the students.